2021
DOI: 10.1186/s12931-021-01759-z
|View full text |Cite
|
Sign up to set email alerts
|

Raised sputum extracellular DNA confers lung function impairment and poor symptom control in an exacerbation-susceptible phenotype of neutrophilic asthma

Abstract: Background Extracellular DNA (e-DNA) and neutrophil extracellular traps (NETs) are linked to asthmatics airway inflammation. However, data demonstrating the characterization of airway inflammation associated with excessive e-DNA production and its impact on asthma outcomes are limited. Objective To characterize the airway inflammation associated with excessive e-DNA production and its association with asthma control, severe exacerbations and pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…This pathway is consistent with transcriptomic studies implicating inflammasome activation in non-T2 asthma, (17,32) and sputum analyses showing elevated IL-1β levels together with caspase activity, neutrophilic inflammation, and neutrophil extracellular traps. (33,34) However, IL-1β mod signaling was not associated with a distinct non-T2 endotype in our study. Instead, IL-1β mod cytokines were co-expressed with T2 cytokines in cluster 3.…”
Section: Discussioncontrasting
confidence: 74%
“…This pathway is consistent with transcriptomic studies implicating inflammasome activation in non-T2 asthma, (17,32) and sputum analyses showing elevated IL-1β levels together with caspase activity, neutrophilic inflammation, and neutrophil extracellular traps. (33,34) However, IL-1β mod signaling was not associated with a distinct non-T2 endotype in our study. Instead, IL-1β mod cytokines were co-expressed with T2 cytokines in cluster 3.…”
Section: Discussioncontrasting
confidence: 74%
“…We recently reported that increased extracellular DNA production in asthmatic airway, a collateral mechanism of airway neutrophilic inflammation, indicates a broad lung function impairment including SAD. 6 So far, therapies targeting neutrophilic airway inflammation in asthma failed to improve asthma outcomes, 41 leaving the complicated role of airway neutrophilic inflammation in asthma and SAD uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…4 When considering the count of sputum neutrophils in this classification, eosinophilic asthma can be further subdivided into eosinophilic or mixed granulocytic, whereas noneosinophilic asthma can be subdivided into neutrophilic or paucigranulocytic. 4 Although both eosinophils and neutrophils, separated or combined, have been incriminated in asthmatic airway inflammation, 5,6 they might have different impacts on asthma severity, symptom control, and lung function impairment. 4 For instance, a recent study has shown that predominant mixed granulocytic asthma indicates worse lung function (forced expiratory volume in 1 second [FEV1]) than the other phenotypes.…”
Section: Abbreviations Usedmentioning
confidence: 99%
“… 56 In addition, increased levels of extracellular DNA in sputum that negatively correlated with FEV 1 % was noted in NA patients with the exacerbation-susceptible phenotype. 47 Moreover, our group clarified epithelial-derived molecules (S100 calcium-binding protein A9 and serum amyloid A1), which were higher in the sera of NA, could induce NETs, further increasing neutrophilic airway inflammation. 57–59 Taken together, NETs are a key mediator of ongoing neutrophilic activation/degranulation, becoming an additional therapeutic target for NA.…”
Section: Novel Targets For Samentioning
confidence: 87%
“… 46 In response to IL-8, phorbol myristate acetate (PMA), or LPS, activated neutrophils released a web-like structure called NETs, which were made up of DNA and granule proteins. 47 , 48 To date, three major mechanisms have been shown to induce NET formation: NADPH oxidase 2 (Nox2)-dependent pathway with PMA stimulation, Nox2-independent pathway with A23187 or ionomycin stimulation, and mitochondrial ROS-dependent pathway with LPS or complement factor C5a receptor stimulation. 49 Currently, the significance of NETs is emphasized in various diseases including cardiovascular disease, metabolic diseases, certain septic conditions, autoimmune, and inflammatory diseases.…”
Section: Novel Targets For Samentioning
confidence: 99%